PENGARUH KUALITAS PENERAPAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN DI INDONESIA (PERIODE 2017-2019) - Salina Salina; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2021)
This study aims to determine the effect of the quality of the implementation of good corporate governance on financial performance in banking companies in Indonesia (2017-2019 period). This research uses a quantitative method approach. The location of the research is carried out on the Indonesia Stock Exchange which is taken from financial reports and annual reports which can be accessed through www.idx.co.id. The analytical method used in this research is simple linear regression with the SPSS for windows 16 application. Based on the analysis results obtained 25 companies that meet the criteria and are sampled. The results showed that simultaneously the Quality of Good Corporate Governance (GCG) Implementation has an effect on Return on Assets (ROA), Net Interest Margin (NIM) and Operational Expenses on Operational Income (BOPO). Meanwhile, partially, the Quality of Good Corporate Governance (GCG) Implementation has a positive and significant effect on Return on Assets (ROA). The Quality of Good Corporate Governance (GCG) Implementation has no effect on Net Interest Margin (NIM). The quality of the implementation of Good Corporate Governance (GCG) has a positive and significant effect on Operational Expenses on Operating Income (BOPO).Keywords: Good Corporate Governance, Return on Assets, Net Interest Margin and Operating Costs and Operating Income.